(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Faculty development has become an essential part of any medical college for effective teaching-learning session. Centre for Medical Education (CME) has been organizing ‘teaching methodology’ workshop to train up the medical teachers in Bangladesh as a part of the faculty development programme. Objectives: To assess the students’ views regarding teaching performances of the teachers who had attended the workshop of CME. Materials and Methods: A cross-sectional descriptive study was conducted in thirteen selected medical colleges of Bangladesh. Students’ opinions were collected by a structured questionnaire of 5-point Likert scale that included 13 separate positive statements regarding teaching performances. For each statement, the mean score was calculated and interpreted as, excellent ≥ 4, Good ≥ 3 to ≤ 4, satisfactory ≥ 2 to ≤ 3, unsatisfactory ≤ 2. But mean score ≤3 indicates deficit aspect of performances. Results: According to students’ aggregated views, teaching performances of 15% teachers were excellent, 51% were good, 25% were satisfactory and 9% were unsatisfactory. Conclusion: The trained teachers are not practising the expected standards in the tutorial classes in all aspects. Initiatives should be taken to pay more attention to deficit aspect of performances. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 46-49